THE EFFECT OF SERVICE QUALITY AND PROMOTION STRATEGIES ON CONSUMER SATISFACTION (Case Study on Consumers at SFA Steak & Resto Karanganyar) - Yumn Umaymah Rasyidah; Mohammad Zaenal Abidin (Islamic Business and Management Journal, 2022)
The purpose of this study is to test and analyze the extent to which the quality of service and promotion strategies implemented by SFA Steak & Resto Karanganyar whether the effect on increasing customer satisfaction. Researchers use this type of research causal quantitative research methods. This research instrument uses a questionnaire that has been distributed to respondents SFA Steak & Resto Karanganyar customers. Samples were taken by 100 respondents using techniques Non-Probability Sampling and the approach Incidental Sampling. Data were analyzed using multiple linear regression analysis to find out which variable between service quality and promotion strategies was the most dominant influence on consumer satisfaction. Based on the results of this study, shows that partially the quality of service variables significantly positive effect on customer satisfaction. This can be proved by the results of the t-test statistics for service quality variables with at count of 2.714 with a significant value of 0.008 smaller than 0.05 (0.008 <0.05), and the regression coefficient has a positive value of 0.095. While the promotion strategy variable does not significantly influence consumer satisfaction. This can be proven by the results of the t-test statistics for the promotion strategy variable with at count of 1.560 with a significant value of 0.122 greater than 0.05 (0.122> 0.05), and the regression coefficient has a positive value of 0.071.The purpose of this study is to test and analyze the extent to which the quality of service and promotion strategies implemented by SFA Steak & Resto Karanganyar whether the effect on increasing customer satisfaction. Researchers use this type of research causal quantitative research methods. This research instrument uses a questionnaire that has been distributed to respondents SFA Steak & Resto Karanganyar customers. Samples were taken by 100 respondents using techniques Non-Probability Sampling and the approach Incidental Sampling. Data were analyzed using multiple linear regression analysis to find out which variable between service quality and promotion strategies was the most dominant influence on consumer satisfaction. Based on the results of this study, shows that partially the quality of service variables significantly positive effect on customer satisfaction. This can be proved by the results of the t-test statistics for service quality variables with at count of 2.714 with a significant value of 0.008 smaller than 0.05 (0.008 <0.05), and the regression coefficient has a positive value of 0.095. While the promotion strategy variable does not significantly influence consumer satisfaction. This can be proven by the results of the t-test statistics for the promotion strategy variable with at count of 1.560 with a significant value of 0.122 greater than 0.05 (0.122> 0.05), and the regression coefficient has a positive value of 0.071.